Determining The Motivating Factors For The General Use Of Social Media Amongst Tourists To South Africa - Mostert, Clarise (My University, 2016)
The remarkable growth in information technology has led businesses to appreciate the power and potential of online marketing, rather than merely focussing their promotional activities and goals on production and sales. Social media has proved to be one of the most effective forms of online marketing, seeing that it allows the business to respond to customer problems instantaneously, customers are amenable to marketing messages, and it assist businesses indirectly to find customers they did not know existed. There is a profound lack of research in the South African context with regard to identifying the motivating factors for the general use of social media. The purpose of this research article was two-fold: firstly to determine a demographic profile of social media users, and secondly to identify the main motivating factors for the general use of social media amongst tourists to South Africa. Research was conducted by means of distributing selfadministered questionnaires at the O.R Tambo International airport, as the main target group was tourists. The completed questionnaires were used for the statistical analysis, which included factor analysis. The results indicated six factors motivating the general use of social media: content sharing, accessing information, connecting and communicating, personal attainment, ease of accessibility, and cost. It is imperative for organisations to understand the factors motivating users to engage in social media, as this will assist organisations to develop social media marketing strategies that will ensure the effective reach of their target markets. By understanding the motivating factors and developing marketing strategies accordingly, the development of sound long-term relationships between the organisation and the users could be established.
full text
Keywords: Social media, motivating factors, marketing, tourism, South Africa. JEL Classification: M31, Z32